Investigação de experiências de pensamento científico de estudantes em tarefas de Física em grupo - Alexandre Fagundes Faria (2016)
The development of scientific thinking is a contemporary learning demand, considering the indications about learning goals for high school courses made by researchers and by entities around the world. Scientific thinking involves domain-specific knowledge and domain-general estrategies. We investigated students scientific thinking experiences inphysics tasks on 11th grade classes. We call scientific thinking experiences those in which general-domain strategies were used during physics tasks. We investigated (i) which domain-general strategies the students used to solve a set of specific tasks; (ii) which are the features of students experiences that required these domain-general strategies; (iii) how the classroom context stimulated or inhibited these experiences; (iv) which are the evidences that scientific thinking was developed along a academic quarter (year division). The research was conducted in a Brazilian vocational high school at Belo Horizonte/Minas Gerais on 2014 1st school quarter. Nineteen electronics or computer science students of 11th grade participated as volunteers. These students worked in 5 small groups. We didnt introduce any change in classroom settings, in other words, all activities and all classroom dynamics or instructional strategies were preserved as before our entry in classroom. We used case studies methodology to stablish our researchdesign. We used four data collection instruments: two video cameras to film the students groups; digital voice recorders to gather verbal interaction in each group; a notebook to write about revelant events with our reasearch purpose in mind while we made the audio and video recordings; a camera to take photos of students notebooks, tests and posters made by them in physics classrooms. We selected two of the five groups to collect data for analysis. To chose these groups we tookinto account students assiduousness. We wanted identify groups whose composition didnt change along the school quarter. In data analysis, we made episode maps of a lessons set and made transcriptions of episodes in which the students had scientific thinking experiences. The anlysis of these episodes maps and these transcriptions was based onJohn Deweys Theory of Experience, in which we found elements that allowed us to identify experiences with educative value. Based onthis analytical work, we sought to answer our research questions. Our results show that the students of the two groups used four domain-general estrategies to solve the physics tasks. We found that students scientificthinking experiences were educative experiences, but qualitatively different. This difference was due to the way students interacted with given conditions to solve tasks. We gathered evidences that allow us to tell that students underwent a process of scientific thinking development. These results have implication for research and for teaching: forresearch because the appropriation of Deweys ideas made by us proved promising to approach developmental processes. Moreover, we used the concept of engagement in order to make one of the principles that we used operational to assess the quality of experiences. Our results also have implications for teaching, because our findings sugest that, despitethe indetermination of students experiences, teachers can make great contribution to their development if the teacher remais committed to create rich and diversed contexts favoring reframing educative experiences.